2019
DOI: 10.1172/jci.insight.128577
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of cavernous angioma with symptomatic hemorrhage

Abstract: BACKGROUND. Cerebral cavernous angiomas (CAs) with a symptomatic hemorrhage (CASH) have a high risk of recurrent hemorrhage and serious morbidity. METHODS. Eighteen plasma molecules with mechanistic roles in CA pathobiology were investigated in 114 patients and 12 healthy subjects. The diagnostic biomarker of a CASH in the prior year was derived as that minimizing the Akaike information criterion and validated using machine learning, and was compared with the prognostic CASH biomarker predicting bleeding in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 55 publications
2
68
1
Order By: Relevance
“…Combined contributions of microbiome and plasma biomarkers. We had previously probed the relationship between circulating plasma inflammatory cytokines and angiogenic protein levels, and disease characteristics [17][18][19] . We now tested if the microbial taxa identified as biomarkers of CA ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Combined contributions of microbiome and plasma biomarkers. We had previously probed the relationship between circulating plasma inflammatory cytokines and angiogenic protein levels, and disease characteristics [17][18][19] . We now tested if the microbial taxa identified as biomarkers of CA ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously observed that CA patients have differences in circulating cytokines and other factors related to angiogenesis and inflammation [17][18][19] . We were able to detect direct associations between several CA distinctive bacterial species and plasma proteins implicated in disease activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomarkers have been long sought for early diagnosis of strokes (104)(105)(106)(107), but only with a limited success in ischemic strokes (108)(109)(110). Efforts to define diagnostic biomarkers for hemorrhagic strokes are underway (111)(112)(113)(114). Inflammatory cytokines have been on target as risk factors or biomarkers for stroke (115).…”
Section: Novel Biomarkers Shed Light For the First Time To Predict Thmentioning
confidence: 99%